2015
DOI: 10.1152/ajprenal.00125.2014
|View full text |Cite
|
Sign up to set email alerts
|

Impaired natriuretic response to high-NaCl diet plus aldosterone infusion in mice overexpressing human CD39, an ectonucleotidase (NTPDase1)

Abstract: Kishore BK, Ecelbarger CM. Impaired natriuretic response to highNaCl diet plus aldosterone infusion in mice overexpressing human CD39, an ectonucleotidase (NTPDase1). Am J Physiol Renal Physiol 308: F1398 -F1408, 2015. First published April 15, 2015 doi:10.1152/ajprenal.00125.2014.-Extracellular nucleotides acting through P2 receptors facilitate natriuresis. To define how purinergic mechanisms are involved in sodium homeostasis, we used transgenic (TG) mice that globally overexpress human CD39 (hCD39, NTPDase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Conversely, one can deduce that the same purinergic signaling may play a significant role in the development of clinical conditions in which the sensitivity of the kidney to AVP or aldosterone is altered, such as acquired nephrogenic diabetes insipidus (NDI) or aldosterone escape. In fact, reports from our and other laboratories support this concept [3,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 52%
“…Conversely, one can deduce that the same purinergic signaling may play a significant role in the development of clinical conditions in which the sensitivity of the kidney to AVP or aldosterone is altered, such as acquired nephrogenic diabetes insipidus (NDI) or aldosterone escape. In fact, reports from our and other laboratories support this concept [3,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 52%
“…Confirming the natriuretic potential of extracellular ATP, mice overexpressing human CD39, an ectonucleotidase that hydrolyzes extracellular ATP/ADP to AMP (see sect. IIB and FIGURE 1), showed evidence for an impaired natriuretic response to a high-salt diet and concomitant aldosterone infusion, including potential dysregulation in the expression of NKCC2 and NCC (586). Proposed dysregulation of NKCC2 is reminiscent of enhanced renal NKCC2 expression observed in P2Y 2 Ϫ/Ϫ mice (431,578).…”
Section: Dietary Salt Inhibits the Open Probability Of Enac In Cnt/ccd By Enhancing Apical P2y 2 Receptor Activationmentioning
confidence: 92%
“…Pressure natriuresis plays an important role in regulating salt homeostasis (231). In addition to hemodynamic factors such as medullary blood flow and renal interstitial hydrostatic pressure, the underlying mechanism includes inhibi-tory effects on proximal and distal tubular transport, in part mediated by paracrine factors, including extracellular nucleotides (586). Microdialysis experiments indicated a positive relationship between renal artery perfusion pressure and the concentration of ATP in the interstitial fluid of the kidney cortex (357,382).…”
Section: Role Of Nucleotide Release and P2 Receptors In Pressure Natriuresismentioning
confidence: 99%
“…In recent years, it has been established that extracellular nucleotides, acting through P2Y 2 and P2Y 12 receptors, also play significant roles in the transport of water and sodium in the kidney, mainly by opposing the actions of one or both hormones on the kidney [13,16,18,20,21,23]. We used a transgenic (TG) mouse model globally overexpressing hCD39 including in the kidney, which had elevated tissue and blood levels of adenosine [53] and showed that these mice manifest defective water and sodium handling [42,54]. Under basal conditions, TG mice exhibited impaired urinary concentrating ability despite normal AVP levels and had impaired AVP release in response to water deprivation.…”
Section: Cd39-adenosinergic Axis In Renal Physiologymentioning
confidence: 99%
“…However, as shown in Fig. 1, the released ATP is sequentially hydrolyzed to ADP and AMP by CD39 or NTPDase1 (nucleoside triphosphate diphosphohydrolase-1), which is expressed in vascular and tubular structures of the kidney [40][41][42]. ATP can also be directly hydrolyzed to AMP by nucleotide pyrophosphatases (NPPs), expressed in the kidney [41].…”
mentioning
confidence: 99%